Extracellular ATP Causes ROCK I-dependent Bleb Formation in P2X(7)-transfected HEK293 Cells - Morelli, Anna (The American Society for Cell Biology, 2003)
The P2X(7) ATP receptor mediates the cytotoxic effect of extracellular ATP. P2X(7)-dependent cell death is heralded by dramatic plasma membrane bleb formation. Membrane blebbing is a complex phenomenon involving as yet poorly characterized intracellular pathways. We have investigated the effect of extracellular ATP on HEK293 cells transfected with the cytotoxic/pore-forming P2X(7) receptor. Addition of ATP to P2X(7)-transfected, but not to wt P2X(7)-less, HEK293 cells caused massive membrane blebbing within 1–2 min. UTP, a nucleotide incapable of activating P2X(7), had no early effects on cell shape and bleb formation. Bleb formation triggered by ATP was reversible and required extracellular Ca(2)(+) and an intact cytoskeleton. Furthermore, it was completely prevented by preincubation with the P2X blocker oxidized ATP. It was recently observed that the ROCK protein is a key determinant of bleb formation. Preincubation of HEK293-P2X(7) cells with the ROCK blocker Y-27632 completely prevented P2X(7)-dependent blebbing. Although ATP triggered cleavage of the ROCK I isoform in P2X(7)-transfected HEK293 cells, the wide range caspase inhibitor z-VAD-fluoromethylketone had no effect. These observations suggest that P2X(7)-dependent plasma membrane blebbing depends on the activation of the serine/threonine kinase ROCK I.